(Research on the preparation of dried tropical fruit snack.i.effect of Sulpphite and Storage Periods on Quality of Fruit Leathers) - A. Basrah Enie; Nami Lestari (Balai Besar Industri Agro, 1992)
Research on preparation of dried tropical fruit snacks,fruit leathers,has been conducted.there fruit snack formulations were developed i.e.(1)mixed fruit (banana,papaya,pineapple),(2)guava, and(3)mango.Product were treated with sodium meta bisulphite and strored for 0,1,2,and 3 months.Result show that the moisture content of product were descreased from 14.4%(0 mo)to 10.0%(3 mos),total sugar were descreased from 84.8%to 73.6%and total titratable acidity were relatively unchanged.Vitamin C content were descreased from 7.06(0 mo)to 6.08 mg/100gr (3 mos)for mixeed fruits,29.0 to 2.35 for guava and 5.13 to 4.11 for mango.Bacterial and mould content of samples were descreased during strorage.Microbial content of sulphite-treated samples were relatively lowered than untreated ones.Total bacteria were descreased from 200 CFU g-1 (0 mo) to CFU g-1 (3 mos),and the total mould were descreased from 350 CFU g-1 (o mo) to 5 CFU g-1 (3 mos. Organoleptic test showed that the taste,flavour, texture and colour of product were accepted by the panelists.Samples can be kept for three month without any significant changes.